Saudi dental postgraduate education (2013–2023): demographic shifts and potential employment challenges - Hussam M. Alqahtani; Layan Z. Alqahtani; Nouf H. Almutairi (BMC Medical Education)
Abstract Background Dentistry is essential for oral health, focusing on the diagnosis, prevention, and treatment of oral diseases. In recent decades, Saudi Arabia has expanded its dental education system, adding new dental schools and postgraduate programs to meet the growing demand for professionals. This study provided a detailed analysis of the trends and demographic characteristics of dental postgraduate programs in Saudi Arabia between 2013 and 2023. Methods This retrospective study collected data on dental postgraduate programs from the Saudi Commission for Health Specialties (SCFHS) for the period from January 2013 to December 2023. Data were gathered on program types, gender, nationality, and geographic distribution. Descriptive statistics were used to analyze trends and distributions. Key variables included the number of postgraduate dental specialty programs, enrolled students, and training levels (board, fellowship). Institutional Review Board (IRB) approval was obtained, and the data was processed using Microsoft Excel 2016. Results The study revealed a total of 1,520 dental postgraduates, with a near-equal gender distribution (51.4% males and 48.6% females). Saudi nationals represented 94.8% of board residency graduates, while 2.4% were non-Saudis. Riyadh had the highest concentration of postgraduates, followed by Makkah. A significant increase in postgraduate enrollment was observed, peaking at 398 in 2023. Conclusions The findings indicate significant growth in Saudi dental postgraduate programs, with regional disparities and increasing numbers of graduates. However, this growth raises concerns about potential unemployment among dental postgraduates, as the number of available positions may not match the surge in graduates. Policymakers must evaluate the expanding programs and their potential impact on the Saudi dental workforce.